Conservative therapy of epidural hematoma with atorvastatin combined with glucocorticoids: cases report and literature review - Wu, Chenrui; Tian, Yu; Zhao, Ruichen; Chen, Runfang; Xu, Chuanlin; Huang, Jinsheng; Jiang, Rongcai (Frontiers in Surgery, 2025)
Epidural hematomas (EDH), typically requiring surgery, may be managed conservatively in select patients. We investigated atorvastatin (10 mg/day) combined with dexamethasone (2.25 mg/day) as conservative therapy in six EDH patients (GCS ≥ 13, volume < 30 ml) post-trauma. All patients recovered fully without surgery, and literatures support conservative care for stable EDH. Our findings suggest this combination therapy may promote hematoma absorption. In conclusion, atorvastatin/dexamethasone shows promise as a non-surgical EDH option, warranting further investigation.